Synchronous 3D Imaging of the Medial and Superior Vocal Fold Surface in an excised human Hemilarynx - Veltrup, Reinhard; Angerer, Susanne; Geßner, Elena; Matheis, Friederike; Sümmerer, Emily; Döllinger, Michael; Semmler, Marion (IEEE Transactions on Biomedical Engineering, 2024)
Objective: This study investigates relationships between the oscillation behavior of the medial and superior vocal fold (VF) surfaces during sustained phonation in a human cadaver hemilarynx. Methods: An experimental test stand synchronously captured the medial and superior VF surfaces of a human ex vivo hemilarynx during sustained phonation using two high-speed camera setups in 24 experimental settings. The 3D coordinates of the medial VF surface were reconstructed by triangulation of sewn-in marker points, while laser-based reconstruction was used for the superior VF surface. Correlation analysis and linear regression were used to quantify the connections of the mean and maximal vertical and lateral VF displacements and the VF velocities. Additionally, stepwise linear regression was used to analyze the impact of the measurement variables mean flow rate, adduction and elongation. Results: Strong linear relationships between all of the tested corresponding parameter pairs of the superior and medial VF surfaces were found (p<.001). Mean and maximum vertical displacements of the medial surface were both approximately 50% of the superior surface. The mean lateral displacements for the medial surface were 12% below the superior surface but 12% higher for the maximum values. The mean and maximum VF velocities were 32% and 36% lower for the medial surface. Conclusion: The suggested multi-modal test stand allows efficient, comprehensive analysis of human hemilarynges and provides promising information about the interaction of the different VF areas and opens up the systematic analysis of multiple hemilarynges. Significance: In future, our results could integrate into ENT diagnostics using 3D laryngoscopy where the hidden medial VF surface dynamics may be predicted from the observable superior surface.
CRIS-Team Scopus Importer:2024-09-20
Keywords: 3D Reconstruction; Hemilarynx; Synchronous High-Speed Imaging; Vocal Fold Dynamics

Three-Dimensional Analysis of Vocal Fold Oscillations: Correlating Superior and Medial Surface Dynamics Using Ex Vivo Human Hemilarynges - Veltrup, Reinhard; Angerer, Susanne; Geßner, Elena; Matheis, Friederike; Sümmerer, Emily; Henningson, Jann-Ole; Döllinger, Michael; Semmler, Marion (Bioengineering, 2024)
The primary acoustic signal of the voice is generated by the complex oscillation of the vocal folds (VFs), whereby physicians can barely examine the medial VF surface due to its anatomical inaccessibility. In this study, we investigated possibilities to infer medial surface dynamics by analyzing correlations in the oscillatory behavior of the superior and medial VF surfaces of four human hemilarynges, each in 24 different combinations of flow rate, VF adduction, and elongation. The two surfaces were recorded synchronously during sustained phonation using two high-speed camera setups and were subsequently 3D-reconstructed. The 3D surface parameters of mean and maximum velocities and displacements and general phonation parameters were calculated. The VF oscillations were also analyzed using empirical eigenfunctions (EEFs) and mucosal wave propagation, calculated from medial surface trajectories. Strong linear correlations were found between the 3D parameters of the superior and medial VF surfaces, ranging from 0.8 to 0.95. The linear regressions showed similar values for the maximum velocities at all hemilarynges (0.69–0.9), indicating the most promising parameter for predicting the medial surface. Since excessive VF velocities are suspected to cause phono-trauma and VF polyps, this parameter could provide added value to laryngeal diagnostics in the future.
CRIS-Team Scopus Importer:2024-11-08
Keywords: 3D laryngoscopy; empirical eigenfunctions; hemilarynx; high-speed imaging; laryngeal modeling; mucosal wave propagation; vocal folds